Temperature and Light-Quality-Dependent Regulation of Freezing Tolerance in Barley - Ahres, Mohamed; Gierczik, Krisztián; Boldizsár, Ákos; Vítámvás, Pavel; Galiba, Gábor (Plants (Basel, Switzerland), 2020)
It is established that, besides the cold, incident light also has a crucial role in the cold acclimation process. To elucidate the interaction between these two external hardening factors, barley plantlets were grown under different light conditions with low, normal, and high light intensities at 5 and 15 °C. The expression of the HvCBF14 gene and two well-characterized members of the C-repeat binding factor (CBF)-regulon HvCOR14b and HvDHN5 were studied. In general, the expression level of the studied genes was several fold higher at 5 °C than that at 15 °C independently of the applied light intensity or the spectra. The complementary far-red (FR) illumination induced the expression of HvCBF14 and also its target gene HvCOR14b at both temperatures. However, this supplementation did not affect significantly the expression of HvDHN5. To test the physiological effects of these changes in environmental conditions, freezing tests were also performed. In all the cases, we found that the reduced R:FR ratio increased the frost tolerance of barley at every incident light intensity. These results show that the combined effects of cold, light intensity, and the modification of the R:FR light ratio can greatly influence the gene expression pattern of the plants, which can result in increased plant frost tolerance.
Keywords: frost tolerance; far-red light; HvCBF14; barley; LED lighting; low temperature; CBF regulon